2022
DOI: 10.1061/(asce)be.1943-5592.0001872
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Condition of Narrow Bridges Using Data from Rotation-Based and Strain-Based Bridge Weigh-in-Motion Systems

Abstract: This study investigates the concept that, when localised bridge superstructure damage is present, the weights of passing vehicles inferred from a rotation-based Bridge Weigh-in-Motion (B-WIM) system will deviate from those predicted by a strain-based B-WIM system. Rotation measurements were gathered from a 5.4 m simply-supported laboratory model bridge crossed repeatedly by a 4-axle model vehicle. Damage was incorporated by bolting stiffening plates onto localised sections of the test bridge. This 'negative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…When the results of these algorithms are incorrect, one can also correct the results of the data labels. It is also necessary to classify these data by anomaly type [ 14 ]. In general, these types of anomalous data are derived and different strategies are adopted to deal with them, as shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the results of these algorithms are incorrect, one can also correct the results of the data labels. It is also necessary to classify these data by anomaly type [ 14 ]. In general, these types of anomalous data are derived and different strategies are adopted to deal with them, as shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also necessary to classify these data by anomaly type [ 14 ]. In general, these types of anomalous data are derived and different strategies are adopted to deal with them, as shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Huseynov et al 73 utilized a 2D model similar to Figure 12(b). It is made up of a 1D beam simply supported over 6 m span and five transverse point loads to mimic a 5-axle vehicle.…”
Section: Bhm Using Traditional B-wimmentioning
confidence: 99%
“…11,12 Hence, there is a possibility of obtaining an inaccurate estimation of GVW using strain-based B-WIM system depending on the damage location. To check the effect of damage near strain sensor, Huseynov et al 73 plotted the response captured by strain sensor at 1/4 L as shown in Figure 17(c). It is found that the strain sensor provides much higher response time history than that of undamaged state.…”
Section: Bhm Using Traditional B-wimmentioning
confidence: 99%
See 1 more Smart Citation